2020
DOI: 10.1038/s41598-020-62557-z
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Domain of Two-component System Sensor Kinase VanS from Streptomyces coelicolor Binds Vancomycin at a Newly Identified Binding Site

Abstract: The glycopeptide antibiotic vancomycin has been widely used to treat infections of Gram-positive bacteria including Clostridium difficile and methicillin-resistant Staphylococcus aureus. However, since its introduction, high level vancomycin resistance has emerged. The genes responsible require the action of the two-component regulatory system VanSR to induce expression of resistance genes. The mechanism of detection of vancomycin by this two-component system has yet to be elucidated. Diverging evidence in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
0
10
0
1
Order By: Relevance
“…Our working hypothesis for future work is that the role of AbrB1/B2 could be to detect cell wall damage (similar to VraR/S and LiaR/S) and regulate systems that contribute to the maintain of cell wall integrity such as the van cluster whose TCS (VanR/S) directly detects vancomycin molecules ( Koteva et al, 2010 ; Novotna et al, 2015 ; Lockey et al, 2020 ) and promotes cell wall remodeling. Thus, a preliminary experiment testing the susceptibility to penicillin G agrees with the working hypothesis, being the Δ abrB mutant more sensitive to this ß-lactam ( Supplementary Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our working hypothesis for future work is that the role of AbrB1/B2 could be to detect cell wall damage (similar to VraR/S and LiaR/S) and regulate systems that contribute to the maintain of cell wall integrity such as the van cluster whose TCS (VanR/S) directly detects vancomycin molecules ( Koteva et al, 2010 ; Novotna et al, 2015 ; Lockey et al, 2020 ) and promotes cell wall remodeling. Thus, a preliminary experiment testing the susceptibility to penicillin G agrees with the working hypothesis, being the Δ abrB mutant more sensitive to this ß-lactam ( Supplementary Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Use of pTTQ18His as expression plasmid has resulted in a high degree of success for producing intact SHKs compared with members of other membrane protein families, including successful expression of 15 of the 16 genome complement of membrane SHKs of Enterococcus faecalis [ 34 ], VanS (A-type) of E. faecium [ 75 , 89 ], BlpH, and ComD2 pheromone-sensing SHKs of Streptococcus pneumoniae (together with several other membrane proteins associated with antimicrobial resistance) [ 90 ] and the PrrB (or RegB) redox-sensing SHK protein of the Gram-negative bacterium Rhodobacter sphaeroides [ 87 , 91 ]. Other membrane overexpression plasmids include pT7-7 [ 92 ] based on T7 polymerase [ 93 ], pProEX available commercially [ 94 ] and pETCH [ 95 ] derived from SUMO fusion vectors [ 96 ]. Many studies have opted to express SHK genes as synthetic codon-optimised genes, though high success rates were obtained with plasmid pTTQ18His using the native gene sequences from both Gram-positive and Gram-negative species.…”
Section: Methodology For Producing Purified Active Forms Of Full-length Membrane Shksmentioning
confidence: 99%
“…Studies of other more distantly-related VanS sensors such as VanS B and VanS SC also revealed direct interactions with vancomycin [ 94 , 138 ], or a signalling complex involving vancomycin [ 139 ]. As mentioned earlier, Koteva et al (2010) reported a k d value of 56 µM for the in vivo binding of a vancomycin photoaffinity probe with actinomycete VanS SC [ 138 ], a value comparable to the weak binding strengths observed for VanS A [ 134 ], whilst Lockey et al (2020) demonstrated direct interactions between full-length VanS SC and vancomycin in vitro, and identified regions of the extracellular sensory domain as the interacting site [ 94 ].…”
Section: Identification and Characterisation Of Signalling Ligands And Inhibitors Using Full-length Shksmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo a OMS, existiam 70 vacinas em desenvolvimento. E, qualquer candidato a vacina teria que direcionar os recursos presentes nos dois tipos de vírus: S e L identificados por pesquisadores de Pequim em pacientes infectados, para ser eficaz (LOCKEY C, et al, 2020). Esforços e ensaios clínicos de fase 1 para desenvolvimento de novas vacinas, estavam em andamento no Reino Unido, Estados Unidos, Alemanha, França e China.…”
Section: Tratamentounclassified